Assessment of correlation relationships between the level of mortality of the population of Zhytomyr region of Ukraine from non-infectious diseases and sanitary-chemical indicators of safety and quality of drinking water - О.S. Zablotska; І.M. Кyrytchuk; N.S. Shcherba; І.М. Nikolaieva (Medičnì Perspektivi, 2023)
The purpose of the publication was to assess the strength and direction of correlation relationships between mortality rates from non-communicable diseases of the population of Zhytomyr region of Ukraine and sanitary-chemical indicators of safety and quality of drinking water. The need for this study was determined by the necessity to adjust existing and develop new strategic approaches to the prevention of non-communicable diseases that depend on the level of chemical contamination of drinking water. The study was conducted in 2016-2020. Standardized indicators of mortality from non-communicable diseases (per 100,000 population) were analyzed. 25375 water samples were studied, among them 8339 belonged to centralized and 17036 – to decentralized water supply. The strength and direction of correlation relationships between population mortality rates from non-communicable diseases and the average values of sanitary-chemical indicators of drinking water were determined by Pearson's linear correlation coefficients and the Chaddock scale. The statistical significance of the correlation coefficients was determined by Student's t-test. In the process of research work such methods as: bibliographic, medical and sociological, retrospective, epidemiological, statistical, system analysis and generalization were used. Statistically significant (p˂0.05) strong direct correlations were found between mortality rates of the urban population of Zhytomyr region from diseases of the circulatory system (I00-I99) (including myocardial infarction) (I21-I22), coronary heart disease (I20-I25), of digestive organs (K00-K93) and average total iron and total hardness values; between nervous system diseases (G00-G99) and average values of manganese in drinking water of centralized water supply, as well as between mortality rates of rural population from diseases of the circulatory system (I00-I99) and average values of total hardness, total iron and nitrates in drinking water of decentralized water supply. The urgent need to develop new strategic approaches to improve the quality of drinking water in the region as one of the factors in the prevention of non-communicable diseases has been proved.